What We See, What We Don't See: Data Governance, Archaeological Spatial Databases and the Rights of Indigenous Peoples in an Age of Big Data - Gupta, Neha; Blair, Sue; Nicholas, Ramona (Journal of field archaeology, 2020)
Archaeological spatial databases have the potential to enable deep insights into human history. These compilations of data are at the interface of data management and data visualization. Yet issues of data governance such as the nature, management, quality, ownership, security, and accessibility of archaeological spatial databases are under examined in archaeology, a situation that can affect data intensive methods and "big" data approaches. Data governance including laws and policies associated with data have bearing on archaeological practices which, in turn, can impact map visualizations and subsequent decision-making. With the growth of the geospatial web and Web 2.0 technologies, there are increasing opportunities for archaeologists and the general public to collect and engage with digital archaeological data. In Canada, greater numbers of specialists from different sectors (research and education, government, private companies) now accumulate, store, and process digital archaeological data. We draw from the OCAP® (ownership, control, access, possession) principles to shed light on data governance in archaeology, with a focus on archaeological spatial databases in Canadian archaeology. In this context, we draw attention to the rights of Indigenous peoples, the legal and policy issues associated with archaeological spatial databases, and a need for greater engagement with Indigenous data governance principles.